Foundations of pragmatic legal linguistics - Galdia, Marcus (Comparative Legilinguistics, 2022)
In this review essay, I describe some basic problems in the research into the legal language that are methodologically connected to linguistic and philosophical pragmatics. I call this area of knowledge pragmatic legal linguistics. Pragmatic legal linguistics deals with the processes that are constitutive of the emergence of meaning in law. Its basic concepts are coined in the course of developments in linguistic and philosophical pragmatics. It applies pragmatic theoretical approaches to clarify the functioning of the legal language and discovers new areas of pragmatic relevance in the research into the legal language. The final goal of pragmatic legal linguistics is to re-formulate our laws in accordance with linguistic findings about the use of language.